Penatalaksaan Skabies Dengan Pendekatan Kedokteran Keluarga Pada Pasien Dewasa - Kumarayanti, Ni Komang Dessy; Hapsari, Yunita; Ramdhani Kusuma, Dinie (Jurnal Kedokteran, 2020)
Scabies is an infected skin disease caused by infestation and sensitization of Sarcoptes scabiei var. Hominis and its products with nocturnal pruritus as symptom. At 2017, scabies was included to Neglected Tropical Diseases (NTD). This disease related to low economic state, low educational level, poor hygiene, linited access to clean water, dense settlement, wrong diagnosis and treatment. Scabies can easily transmitted both directly and indirectly. Scabies was neglected by people because people thought thah this disease wasn’t a life-threatening disease, however this disease can lead to some complications such as impetigo, celullitis, abscesses, even sepsis, in the case of S. pyogenes, post-streptococcal glomerulonephritis and acute rheumatic fever can happen. In resource-poor countries, outbreaks of acute poststreptococcal glomerulonephritis coincide with outbreaks of scabies and may contribute to development of chronic kidney disease and subsequent renal failure. Patient came with complaints itching between fingers on both hands and foots, wrist, back, and crotch especially at night since four months ago. He has poor personal hygiene. The patients was diagnosed with scabies, then he got treatment with family medicine approach. Medicine treatment he got was Permethrine cream 5%, Cetirizine tablet, and mixed cream of Fusidat Acid and Desoximetason. The family who lived together with patient also got treatment and educated about the disease.